PELAYANAN PUSAT KESEJAHTERAAN SOSIAL (PUSKESOS) DALAM PENANGGULANGAN KEMISKINAN (Studi di Kelurahan Abeli Dalam Kecamatan Puuwatu Kota Kendari) - Jamaluddin, Jamaluddin; Bahtiar, Bahtiar; Sarmadan, Sarmadan (WELL-BEING: Journal of Social Welfare, 2021)
This study aims to determine the services of social welfare centers (Puskesos) in poverty reduction in Abeli Dalam Village, Puuwatu District, Kendari City. This type of research is a qualitative descriptive study. The data collection technique was carried out by means of observation, interviews, and documentation with 13 research informants. 5 people from the implementation team of the social welfare center (Puskesos), and 8 additional informants, 1 TKSK and 7 community members who are beneficiaries of Puskesmas services in Abeli Dalam Village, Puuwatu District, Kendari CityThe results showed that social welfare center services (Puskesos) are located in Abeli Dalam Village government by providing social welfare center services in the program including: Healthy Idonesia Card (KIS), Family Hope Program (PKH), Non-Tunia Food Assistance (BPNT), and Cash Social Assistance (BST). which is carried out by Puskesmas to the poor, namely: 1) making changes in the form of activities, these activities are in the form of socialization. 2) assist in overcoming problems, by providing quality service assistance to poor individuals / families / households must have clear, straightforward, easy to understand and implement procedures. These activities include; receiving complaints, checking the status of potential beneficiaries with data validation and verification processes, complaint handling services according to program needs, in this case the KIS, PKH, BPNT, BST programs, and handling referrals. With 700 KIS recipients, 77 PKH family heads, 137 BPNT family heads, and 6 BST family heads. The number of service recipients for the poor was 174 households out of 202 households. These are found in Puskesmas services as well as the benefits of puskesmas services for the community that can have a good impact on community welfare and poverty reduction, and contribute to the fulfillment of the right to access health services, education, basic food assistance, and cash social assistance can be achieved